Environmental Damage as a Loss to the State Economy in the Perspective of State Control Rights - Siti Chusnul Nurlaela; Andik Puja Laksana; Ade Saptomo (Warmadewa Press, 2025)
Environmental damage can be considered a loss to the state economy. In terms of analyzing the state economy, the author takes the perspective of state control rights. The Constitution of the Republic of Indonesia in Article 33 paragraph (3), which states that the earth, water and natural resources are controlled by the state and properly managed for the greatest prosperity of the people. This should be referred to as a philosophical guideline because the management and administration of the state economy must and must have aspects of concern for the prosperity of the people Observed from the sustainability of the state's operational activities in building a climate of public services recorded in 2018, the state issued a balance of Rp. 112 trillion, with an increase from the previous year, namely in 2014 to 2017 with a total of only Rp. 115 trillion. This in a year beats the expenditure that is consumable and the tendency to do repeated procurement from the total of the past three years. The view of wasting costs for a kind of environmental rehabilitation must be used with the prefix of mitigation, contextually the state is obliged with its role to maximize the right to state control to prevent negative extreme damage to the environment. This research is studied and made with normative legal research methods, explicitly using a statutory approach (statuate approach), and a conceptual approach (conceptual approach). The statutory approach is chosen by the author to analyze the problem with relevant regulations and regulations, so that this research has an analytical technique that is based on positive law in Indonesia.